Chemical Composition of the Eggs of the Freshwater Turtle Phrynops hilarii (Chelidae: Testudines) - Prieto, Yanina (2019)
At oviposition, amniote eggs contain all the nutrients required for complete neonate tissue development. For reptiles and birds, the egg yolk is the main embryonic energy source and is composed predominantly of proteins and lipids, while also providing essential inorganic ions including calcium (Ca), potassium (K), and magnesium (Mg), and trace elements such as zinc (Z) and iron (Fe). Despite the fact that the Hilaire’s Toadhead Turtle, Phrynops hilarii, is one of the most representative and widely distributed turtle species in Argentina, there are very few studies regarding its reproductive biology. The objectives of this work were to (1) describe the morphological characteristics of Phrynops hilarii eggs, specifically egg and yolk size; (2) determine the relative proportions of egg yolk components (water, ash, lipids, proteins, and minerals); and (3) examine the relationships between egg size, yolk size and yolk components. We collected 171 eggs from 11 individual nests during the 2012 March-April reproductive season. We analyzed one egg per clutch (n = 11) to determine the egg yolk chemical composition. Yolks were composed of 58.3% water, while the dry component was 2.7% ash, 24.9% lipids, and 56.7% protein. The most abundant macromineral detected was K (0.63%) and the most abundant trace mineral was Mg (0.13%). We did not find associations between egg measurements and components, but there were many significant correlations between egg components. Data we collected for this study are important to begin to understand the roles of different nutrients in embryonic development and to further explore maternal investment patterns in Phrynops hilarii.